The Quantitative analysis of the dynamics and structure of terminologies - Kageura, Kyō, 1964- (Terminology and lexicography research and practice., 2012)
The dynamics and systematicity of terminology: this book addresses these essential and intriguing aspects of terminology, by using quantitative methodologies which have been underutilized in the field to date. Through the analysis of the Japanese terminologies of six domains and with special reference to the dynamic behaviour and the status of borrowed and native morphemes, the book reveals: (a) how borrowed and native morphemes contribute to the construction of these terminologies, and how these contributions are likely to change as the terminologies grow; (b) how borrowed and native morpheme.